2011
DOI: 10.3109/17453674.2011.581264
|View full text |Cite
|
Sign up to set email alerts
|

Pain control after total knee arthroplasty: a randomized trial comparing local infiltration anesthesia and continuous femoral block

Abstract: Background and purposePain after total knee arthroplasty (TKA) is usually severe, and epidural analgesia or femoral nerve block has been considered to be an effective pain treatment. Recently, local infiltration analgesia (LIA) has become increasingly popular but the outcome of this method regarding the analgesic effect has not been fully evaluated. We compared local infiltration analgesia and femoral block with regard to analgesia and morphine demand during the first 24 h after TKA.Methods40 patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
129
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 32 publications
2
129
0
4
Order By: Relevance
“…This study found lower pain scores for the first 8 hours after surgery in the periarticular injection group and no difference thereafter [9]. Other similar studies found opposing results: Carli et al [8] found no differences in pain scores and Toftdahl et al [34] and Affas et al [2] found lower scores in patients receiving periarticular injection compared with those receiving isolated femoral nerve blocks during the first postoperative day [2,8,34]. The use of combined sciatic and femoral nerve blocks over femoral nerve block alone has been shown to have improved pain scores and seems more beneficial for pain management [1,10,17].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This study found lower pain scores for the first 8 hours after surgery in the periarticular injection group and no difference thereafter [9]. Other similar studies found opposing results: Carli et al [8] found no differences in pain scores and Toftdahl et al [34] and Affas et al [2] found lower scores in patients receiving periarticular injection compared with those receiving isolated femoral nerve blocks during the first postoperative day [2,8,34]. The use of combined sciatic and femoral nerve blocks over femoral nerve block alone has been shown to have improved pain scores and seems more beneficial for pain management [1,10,17].…”
Section: Discussionmentioning
confidence: 51%
“…It also was adequately powered and relatively homogeneous; we excluded patients who previously had one of the techniques used with prior knee surgery (which excluded a surprisingly large number of patients) and also excluded patients who were narcotic-tolerant. Additionally, we evaluated patients beyond the hospitalization for any neurologic complications related to the procedure, something many prior studies have not done [2,9,34,36]. Before the initiation of this study, our routine pain management technique after knee arthroplasty was the use of peripheral nerve blocks together with multimodal medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its success improving the quality of life of patients with arthritis [31], pain after TKA can sometimes be severe and difficult to control [1]. Clinical studies have shown that severe postoperative pain can be associated with an increased risk of complications, including rehabilitation delay [59], prolonged return to normal functioning [27,28], progression to persistent pain states [46,68], prolonged hospital stay [49], and increased readmission rate [21], all of which can lead to increased cost of care [4,42,62,69].…”
Section: Introductionmentioning
confidence: 99%
“…Of those studies excluded, Affas et al performed an RCT of 40 patients comparing intra-operative local anaesthetic infiltration to pre-and post-operative femoral nerve block (via a perineural catheter). 17 They reported a marginal reduction in pain at rest in the group receiving local anaesthetic infiltration (NRS 1.6 vs 2.1), a statistically significant increase in incidence of intense pain in the femoral nerve block group (1/20 vs 7/19 patients reporting an NRS pain score of >7, p = 0.04) and concluded that although both methods provided good analgesia, local anaesthetic infiltration 'may be considered to be superior to femoral nerve block as it is cheaper and easier'. These findings are supported by Toftdahl et al, who, in their RCT of 80 patients found that those receiving peri-articular infiltration and postoperative infusion of local anaesthetic had lower morphine consumption (83 mg vs 100 mg, p = 0.02) and improved mobility on the first post-operative day (29/39 vs 7/27 able to walk > 3m, p < 0.001).…”
Section: This Study In Relation To Other Studies and Future Researchmentioning
confidence: 99%